2011
DOI: 10.2503/jjshs1.80.372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MA Storage and 1-MCP on Storability and Quality of ‘Sanuki Gold’ Kiwifruit Harvested at Two Different Maturity Stages

Abstract: The effects of modified atmosphere (MA) storage and application of 1-methylcyclopropene (1-MCP) at harvest on the storability and quality of 'Sanuki Gold' kiwifruit harvested at two different maturity stages were investigated. MA storage in both fruit harvested early at 136 days after pollination (DAP) or late at 154 DAP delayed flesh softening, increase in soluble solid concentrations (SSC), decrease in titratable acids (TA), and reduction in fruit flesh color index compared to air stored fruit, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
2
0
3
Order By: Relevance
“…<10 N; Kim et al , 1999 ; Yin et al , 2009 ). In a previous study, it was shown that ‘Sanuki Gold’ kiwifruit softened to ∼20% of firmness at harvest after 1 month of storage at 4 °C under ambient conditions without any detectable ethylene production ( Mworia et al , 2011 ). Similar observations have been reported in ‘Hayward’ kiwifruit ( Manolopoulou et al , 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…<10 N; Kim et al , 1999 ; Yin et al , 2009 ). In a previous study, it was shown that ‘Sanuki Gold’ kiwifruit softened to ∼20% of firmness at harvest after 1 month of storage at 4 °C under ambient conditions without any detectable ethylene production ( Mworia et al , 2011 ). Similar observations have been reported in ‘Hayward’ kiwifruit ( Manolopoulou et al , 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide sequence ACS1 forward 5 -CGGTACTGTTTTTAGCTCTCCAGACT-3 ACS1 reverse 3 -TGGAGTGGCTACTGTCCTTTAGAA-5 ACO3 forward 5 -TGGCAACCAAAGGCCTAGAG-3 ACO3 reverse 3 -GGTGCTTTCCCAGTCCAAATC-5 EIL4 forward 5 -AAATTCACAGTTACATCACGGACCTA-3 EIL4 reverse 3 -GTCCATCACCACTGGGCATAT-5 ERF14 forward 5 -TGGGAACCAACCCCAACA-3 ERF14 reverse 3 -GCCTTTTCCCAACATTTCCTT-5 PGB forward 5 -GGTACAAGTGCCTCCGATGTC-3 PGB reverse 3 -CCTGGCATGGGAACCTCTT-5 18S rRNA forward 5 -GGAACTTGAACAAGAATGCAACAT-3 18S rRNA reverse 3 -GAGAGCAAGCACCACAAGCA-5 vest after 1 month of storage at 4°C under ambient conditions without any detectable ethylene production (Mworia et al, 2011). A similar observation has been reported for 'Hayward' kiwifruit (Manolopoulou et al, 1997).…”
Section: Namementioning
confidence: 99%
“…과실의 산 함량 또한 두 품종 모두 외생 에틸렌 처리 과실에서 무처리 과실보다 빠르게 감소하였다. 프로필렌을 처리한 '사누 키골드', '홍양' 역시 무처리 과실보다 처리 과실에서 산 함량이 빠르게 감소하였다 (Mworia et al, 2011;Murakami et al, 2014). 키위프루트의 주요 유기산 구성은 구연산(40-50%), 퀸산(40-50%), 그리고 말산(10%)이며 (Marsh et al, 2004), 후숙 과정 중 과실의 산 함량 감소는 구연산의 감소에서 기인하는 것으로 보고된 바 있다(MacRae Marsh et al, 2004).…”
Section: Rna 정량분석unclassified
“…키위프루트에서 과실의 경도는 후숙 단계를 나타내는 지표로 사용되는데, 외생 에틸렌의 처리는 과실을 균일하고 빠르게 연 화시킨다고 하였다 (Redgwell et al, 1990;Redgwell et al, 1992;Redgwell et al, 1997;Schröder and Atkinson, 2006;Lim et al, 2017). '골드원'과 '제시골드' 품종의 경도 역시 프로필렌을 처리한 다른 품종과 마찬가지로 외생 에틸렌을 처리한 과실에 서, 그리고 처리농도가 높은 과실에서 빠르게 감소되었다 (Antunes et al, 2000;Mworia et al, 2011;Murakami et al, 2014).…”
Section: Rna 정량분석unclassified
See 1 more Smart Citation